IMPLEMENTASI KEBIJAKAN PENGEMBANGAN KEPROFESIAN BERKELANJUTAN DALAM MENGEMBANGKAN PROFESIONALISME GURU DI SMP NEGERI 2 KEDUNGWUNI KABUPATEN PEKALONGAN - Dian Nur Afiah; Nur Kholifah; Nurkolis Nurkolis (Dharmas Education Journal (DE_Journal), 2024)
The purpose of this study was to further study and investigate the use of long-term professional development in fostering teacher professionalism. The strategy, implementation, and results of the use of PKB as a component of teacher development are the main areas of concern. This study is descriptive and qualitative, and collects data through observation, interviews, and documentation studies. The findings of this study indicate that teacher development must be actively supported and implemented, especially when PKB is used. The principal, vice principal of the curriculum, and the PKB coordinator team meet to coordinate PKB planning. Meanwhile, teacher self-development and inventive work are more realized than the scientific publication component in an effort to improve teacher quality through the implementation of PKB. As part of teacher development management, instructors, students, and the school itself can all feel the impact of Teacher PKB.”